2000
DOI: 10.1021/ac000348c
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Assembled Mass-Transport Controlling Micromembranes and Their Application in Implanted Amperometric Glucose Sensors

Abstract: Micromembranes were assembled by sequentially chemisorbing polyanions and polycations on miniature (5 x 10(-4) cm2) enzyme electrodes. The sequential chemisorption process allowed the simultaneous tailoring of their sensitivity, dynamic range, drift, and selectivity. When assembled on tips of 250-microm-diameter gold wires coated with redox polymer-"wired" glucose oxidase, they allowed tailoring of the glucose electrodes for > 2 nA/mM sensitivity; 0-30 mM dynamic range; drift of < or =5% per 24 h at 37 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 29 publications
0
56
0
Order By: Relevance
“…In each experimental animal, one probe was implanted for a set period of time (3,5, and 7 days) on one side of the dorsal subcutis while another probe was acutely implanted as a control on the opposite side on the day of sample collection. The 3-day implantation experiment has been performed using three animals; the 5-day and 7-day implantation experiments were each performed using two animals.…”
Section: -Deoxyglucose In Vivo Microdialysismentioning
confidence: 99%
“…In each experimental animal, one probe was implanted for a set period of time (3,5, and 7 days) on one side of the dorsal subcutis while another probe was acutely implanted as a control on the opposite side on the day of sample collection. The 3-day implantation experiment has been performed using three animals; the 5-day and 7-day implantation experiments were each performed using two animals.…”
Section: -Deoxyglucose In Vivo Microdialysismentioning
confidence: 99%
“…The calibration and selectivity measurements were performed in a 100 ml polypropylene beaker pretreated overnight in 0.1 M HNO 3 . Only the very tips of the electrodes were immersed into the sample solution.…”
Section: Emf Measurementsmentioning
confidence: 99%
“…Miniaturized sensors have been successfully explored in chemical analysis, including in vivo applications as well as online monitoring bioactive substances [1][2][3][4]. Also due to their compact size, high sensitivity and comparably low cost, microsensors are an attractive system for small volume applications to detect ultra-small amounts of compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Heller and colleagues constructed micrometer scale polyelectrolyte thin films that limited glucose mass transfer in implanted sensors. [31] Others have observed that polyelectrolyte nanocomposite thin films are highly compact, have a nanoporous structure and can limit the diffusion of small molecules such as ferricyanide. [15,16,22] Given that the nanocomposite films described here do undergo significant structural changes upon oxidation and reduction, these films are likely very compact and may posses nanoporosity as seen in other polyelectrolyte thin films.…”
Section: Electron Transfer and Mass Transfer At The Sensor Surfacementioning
confidence: 99%